1976
DOI: 10.1111/j.1476-5381.1976.tb07458.x
|View full text |Cite
|
Sign up to set email alerts
|

Isotonic and Isometric Responses of Differenttonic Muscles to Agonists and Antagonists

Abstract: I With isotonic recording the percentage of muscle shortening as compared with the maximal possible shortening, and with isometric recording the percentage of developed tension were determined. In relatively 'thick' muscles, such as dorsal leech muscle, frog rectus abdominis or protractor pharynx of holothuria (0.3-0.8 mm thick), the concentrations of a full agonist (carbachol) producing a given percentage of tension, (e.g. 50%) are about 5 times greater than the concentrations, producing the same percentage o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1976
1976
1993
1993

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…The diffusion rate of an agent or the thickness of the vein possibly affect the pD2 value (21). For example, the concentration of an agent in the outer region of a tissue may be different from the inner region.…”
Section: Discussionmentioning
confidence: 99%
“…The diffusion rate of an agent or the thickness of the vein possibly affect the pD2 value (21). For example, the concentration of an agent in the outer region of a tissue may be different from the inner region.…”
Section: Discussionmentioning
confidence: 99%
“…The authors suggested that the penetration of ACh to the muscle ChE is hampered when the muscle is contracted and shortened. Michelson & Shelkovnikov (1976) have presented evidence that the isolated rectus abdominis muscle of the frog also hydrolyses ACh more rapidly in an extended state (isometric conditions) than in a shortened state (isotonic recording). Lancaster (1973) added a quaternary ammonium OPI to the bath containing a nerve-muscle preparation of rat diaphragm and observed that in the tetanized muscle the degree of ChE inhibition was less than in the control.…”
Section: Discussionmentioning
confidence: 99%
“…At all muscle lengths, force development in isometric experiments is higher, indicating that in isotonic contraction the smooth muscle does not contract fully (Stephens and Van Niekerk, 1977). This incomplete contraction may be due to thickening of the muscle-hindering diffusion of the neurotransmitter and folding of contractile elements impairing optimal functioning (Michelson and Shelkovnikov, 1976;Stephens and Van Niekerk, 1977). At function residual capacity (FRC) in vivo, the tracheal smooth muscle may be stretched to around L,,, (Moreno et al, 1986).…”
Section: Isometric Isotonic and Auxotonic Recordingmentioning
confidence: 99%